2020
DOI: 10.21203/rs.3.rs-41361/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of dapagliflozin on serum and urinary uric acid levels in patients with type 2 diabetes: a prospective pilot trial

Abstract: Background: We aimed to evaluate the effects of short-term therapy with dapagliflozin on serum uric acid (SUA) and urinary uric acid (UUA) levels in patients with type 2 diabetes.Methods: In this prospective pilot trial, 8 patients with type 2 diabetes mellitus were assigned to the treatment group with dapagliflozin 10 mg once daily for one week, and 7 subjects with normal glucose tolerance were recruited into the control group. Data of anthropometric measurements, SUA, 24-hour UUA, fractional excretion of UA … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…For the use of dapagliflozin, Yuan et al found that SUA levels decreased from 347.75 ± 7.75 μmol/L before dapagliflozin treatment to 273.25 ± 43.18 μmol/L after dapagliflozin treatment, with a statistically significant difference (p = .001), and the SUA-lowering effect of dapagliflozin could be driven by increasing UA excretion within 1 week of treatment, which may be the mechanism of SGLT-2 inhibitors in lowering SUA. 52 In addition, dapagliflozin has early cardiorenal benefits, which included anti-inflammatory, antifibrotic, antioxidative, antiapoptotic properties, renoprotective and haemodynamic effects, as well as attenuation of glucotoxicity, reduction of SUA levels and epicardial adipose tissue, modification of the neurohumoral system and cardiac fuel energetics, and inhibition of the sodium-hydrogen exchange. 53 However, different doses and durations of the same SGLT-2 inhibitor may have different SUA-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
“…For the use of dapagliflozin, Yuan et al found that SUA levels decreased from 347.75 ± 7.75 μmol/L before dapagliflozin treatment to 273.25 ± 43.18 μmol/L after dapagliflozin treatment, with a statistically significant difference (p = .001), and the SUA-lowering effect of dapagliflozin could be driven by increasing UA excretion within 1 week of treatment, which may be the mechanism of SGLT-2 inhibitors in lowering SUA. 52 In addition, dapagliflozin has early cardiorenal benefits, which included anti-inflammatory, antifibrotic, antioxidative, antiapoptotic properties, renoprotective and haemodynamic effects, as well as attenuation of glucotoxicity, reduction of SUA levels and epicardial adipose tissue, modification of the neurohumoral system and cardiac fuel energetics, and inhibition of the sodium-hydrogen exchange. 53 However, different doses and durations of the same SGLT-2 inhibitor may have different SUA-lowering effects.…”
Section: Discussionmentioning
confidence: 99%